Posterior iris-claw aphakic intraocular lens implantation and Descemet membrane endothelial keratoplasty. Issue 9 (29th April 2014) - Gonnermann, Johannes; Maier, Anna-Karina B; Klamann, Matthias K J; Brockmann, Tobias; Bertelmann, Eckart; Joussen, Antonia M; Torun, Necip
Abstract : Purpose: To evaluate clinical outcomes and complications after Descemet membrane endothelial keratoplasty (DMEK) and posterior iris-claw aphakic intraocular lens (IOL) implantation. Methods: This prospective cohort study comprised seven consecutive eyes (seven patients) without adequate capsular support and bullous keratopathy undergoing posterior iris-claw aphakic IOL implantation and DMEK. Corneal transparency, central corneal thickness, endothelial cell density, visual outcomes and complication rates were measured during the follow-up. Results: The iris-claw IOLs were inserted during an IOL exchange in three eyes, and as a secondary IOL implantation in one aphakic eye during DMEK procedure. Three eyes had IOL exchange prior to secondary DMEK. Mean follow-up was 7 months (range 3–14 months). The final best spectacle-corrected visual acuity improved significantly (0.33±0.31 logMAR) compared with the preoperative best spectacle-corrected visual acuity (1.84±0.90 logMAR). The mean endothelial cell loss was 24.8% over the follow-up. Complications included graft dislocation in four eyes; which could be easily reattached with a rebubbling procedure. No graft failures, no cases of pupillary block glaucoma and no IOL dislocations were encountered. Conclusions: DMEK and retropupillar iris-claw IOL implantation provide good visual outcomes with a fast visual recovery and appear to be a feasible method for the management of bullous keratopathy but with higher graft detachment rates. Trial registration number: NCT02020044.